Renal multidector row CT - Kocakoc, E; Bhatt, S; Dogra, VS (W B Saunders Co-Elsevier Inc, 2005)
Multidetector row CT is the most recent advance in CT technology. An increased number of detector rows and more powerful x-ray tubes result in faster scanning time, increased volume coverage, and improved spatial and temporal resolution. MDCT technology allows superior image quality, decreased examination time, and the ability to perform complex multiphase vascular and three-dimensional examinations.
Keywords: Unenhanced Helical Ct; Contrast-Enhanced Ct; Multidetector Ct; Multislice Ct; Spiral Ct; Computed-Tomography; Preoperative Evaluation; Abdominal Compression; Ureteral Stones; Multisection Ct